2013
DOI: 10.6000/1927-5129.2013.09.59
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of Neem Seed on Different Life Stages of Red Flour Beetle, Tribolium castaneum

Abstract: Fine Neem Seed Powder (NSP) was tested in three dozes, viz. 0.5%, 1.0% and 2.0% (w/w) for determination of its toxicity and detrimental effects on life stages of red flour beetle, Tribolium castaneum. Fifty gram treated and untreated (control) wheat was kept in glass jars and 10 pairs of the beetles were released in each. Mortality count was made after 72 hours. LD50 calculated as 1.841% NSP in wheat (w/w). NSP served as an Insect Growth Regulator (IGR). It was observed that at 0.5% dose, the number of larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Das (1987) indicated that neem seed oil showed 100% control of pulse beetles (Callosobruchus chinensis L.) applied at 10 ml/kg grain. Khan et al (2013) showed a positive potential of plant extracts as suitable substitute of conventional synthetic insecticides for the management of insect pest attacking stored commodities. Kumawat and Bhanwar (2013) found that the maximum fortification of insects was attained by neem oil, where no grain injury was recorded by neem oil preserved grains and no adversative effect of plant oils was observed on seed practicality for up to 270 days of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das (1987) indicated that neem seed oil showed 100% control of pulse beetles (Callosobruchus chinensis L.) applied at 10 ml/kg grain. Khan et al (2013) showed a positive potential of plant extracts as suitable substitute of conventional synthetic insecticides for the management of insect pest attacking stored commodities. Kumawat and Bhanwar (2013) found that the maximum fortification of insects was attained by neem oil, where no grain injury was recorded by neem oil preserved grains and no adversative effect of plant oils was observed on seed practicality for up to 270 days of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Kumawat and Bhanwar (2013) found that the maximum fortification of insects was attained by neem oil, where no grain injury was recorded by neem oil preserved grains and no adversative effect of plant oils was observed on seed practicality for up to 270 days of treatment. Tariq et al (2013) concluded that the insect growth inhibition was increased by increasing the dose of neem seed powder from 0.5 % to 1.0 % and 2.0 % (w/w).…”
Section: Introductionmentioning
confidence: 99%